The Influence of Chronic Inflammation on the Development of Atherosclerosis and Cardiovascular Events - Maharaj, Vaishnavi; A M, Srilekshmi; Krishnendu S; Kumar, Sooraj Sunil (Student's Journal of Health Research Africa, 2024)
Background Atherosclerosis, a key contributor to cardiovascular diseases (CVD), is influenced by multiple risk factors. Chronic inflammation has been increasingly recognized as a significant driver in the progression of atherosclerosis and the subsequent development of cardiovascular events. This study investigates the role of chronic inflammation in accelerating atherosclerotic plaque formation and its contribution to cardiovascular complications. Materials and Methods A cohort of 200 patients, selected from various hospitals in Kerala, india aged 40–70 years, with established risk factors for atherosclerosis (hypertension, hyperlipidemia, smoking) were enrolled in this prospective study. Inflammatory markers, including C-reactive protein (CRP) and interleukin-6 (IL-6), were measured at baseline and followed over a 2-year period. All patients underwent carotid intima-media thickness (CIMT) measurements and coronary artery calcium (CAC) scoring as indicators of atherosclerotic burden. The cohort was divided into two groups based on baseline inflammation levels: high inflammation (n=100) and low inflammation (n=100). Cardiovascular events, including myocardial infarction (MI) and stroke, were recorded. Results At the 2-year follow-up, patients in the high inflammation group demonstrated a significant increase in CIMT (mean increase of 0.15 mm) and CAC scores (average increase of 120 points) compared to the low inflammation group (mean increase of 0.05 mm in CIMT and 40 points in CAC). Cardiovascular events were more frequent in the high inflammation group, with 25% experiencing MI or stroke compared to 10% in the low inflammation group. Elevated CRP (>3 mg/L) and IL-6 (>10 pg/mL) were independently associated with a 2.5-fold increased risk of cardiovascular events. Conclusion Chronic inflammation plays a pivotal role in the progression of atherosclerosis and the occurrence of cardiovascular events. Higher levels of inflammatory markers are associated with increased atherosclerotic plaque burden and a greater risk of MI and stroke. Targeting chronic inflammation may provide a novel therapeutic avenue to mitigate the progression of atherosclerosis